Are healthcare workers ready for Ebola? An assessment of their knowledge and attitude in a referral hospital in South India - Ahmad, Akram; Khan, Muhammad Umair; Jamshed, Shazia Qasim; Kumar, Bandari Deepak; Kumar, Gogikar Sudhir; Reddy, Puchchakayala Goverdhan; Ajmera, Sudhakar (Porto Conte Ricerche Research Centre, 2016)
INTRODUCTION: The World Health Organization (WHO) declared the Ebola virus disease (EVD) epidemic to be a public health emergency of international concern. Healthcare workers (HCWs) are at the highest risk of infection, as they may come into contact with patients' blood or fluids. This study was conducted to assess knowledge and attitudes of HCWs towards EVD in India. METHODOLOGY: A descriptive, cross-sectional study was conducted in a multispecialty public sector referral hospital of Telangana, India. Knowledge and attitude of HCWs were evaluated using a pre-validated questionnaire. A sample of 278 participants was selected to participate in this study. The Chi-squared test was used to assess the relationship between attitudes and demographic characteristics. Logistic regression was used examine the association between knowledge and study variables. RESULTS: Of 257 participants who responded (92.4% response rate), 157 (61.1%) were females. The majority of the respondents were physicians (n = 117, 45.5%). Radio and television were the major sources of information about EVD reported by participants (89%). Overall knowledge of HCWs was poor (mean knowledge score: 6.57 ± 2.57). Knowledge of physicians and experienced workers (≥ 10 years) was significantly higher than their respective groups. The overall attitude of the participants was positive (mean attitude score: 1.62 ± 0.57). Significant positive correlations between knowledge and attitude were observed. CONCLUSIONS: The findings indicate that participants lack basic understanding of EVD. We recommend future studies be conducted across India to identify and subsequently bridge the knowledge gaps among HCWs.